(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we made an attempt to crack Goal programming problem by using Modified Gomory Constraint Technique. This method will be a new approach and easy to crack goal programming problem. The above method will be a powerful method to find better solution. It will take less iterations and save our precious time by omiting calculations of net evaluation.